Procedural outcomes and long‐term survival following lead extraction in octogenarians. Issue 7 (16th June 2017) - El‐Chami, Mikhael F.; Sayegh, Michael N.; Patel, Adarsh; El‐Khalil, Jad; Desai, Yaanik; Leon, Angel R.; Merchant, Faisal M.
Abstract: Background: Octogenarians account for a significant percentage of patients with indwelling pacemakers or defibrillators. Objectives: To determine procedural outcomes and long‐term survival after lead extraction (LE) in octogenarians. Methods: We retrospectively identified all patients who underwent defibrillator or pacemaker LE at our institution between January 1, 2007 and May 31, 2016. Patients were stratified based on age into two groups: <80 years old (Group 1, n = 674) or ≥80 (Group 2, n = 100). Outcomes were determined by medical records review and query of the Social Security Death Index. Results: Patients in Group 2 were more likely to be hypertensive (77% vs 61%, P = 0.02), more like to have coronary artery disease (50% vs 39%, P = 0.049), and more likely to be extracted for infectious indications (47% vs 33%, P = .009). The number of leads extracted per procedure was 2.0 ± 0.8 and the mean dwell time of the oldest extracted lead was 5.6 ± 4.3 years, without significant differences between groups. Extraction procedure success (Group 1: 94.7%, Group 2: 96%, P = 0.808) and procedural deaths (Group 1: 0.9% vs Group 2: 0%, P = 1.0) were similar. There was no significant difference in survival up to 3 years following LE between groups. Conclusion: At experienced centers, LE can be performed safely in octogenarians with procedural success rates and long‐term survival comparable to younger individuals.